Ten theories about persistent vegetative state - Cattorini, Paolo (Medicina e Morale, 1994)
The patient in persistent vegetative state (Pvs) is a living human being, who keeps the same inherent dignity of other patients, but cannot perform relational activities, because of the disease. Pvs patients must be treated as persons and cared for through the most proportionate means. The author stresses the close union between personal human life and the biological Iife of the human organism as a whole: it is the same organism that develops its superior capacities in a continuous progression from conception to adulthood and that may be impaired by illness. The notion of the so-called "neocortical death" is criticized: such theirs, to be consistent, should regard Pvs patients not only as non-persons, but also as non-humans. On the contrary, ''whole brain death" is defended, in the light of the present medical data. The author also examines other issues debated in today's bioethical discussion on the notion of death: the possibility of substituting some brain functions, the hypothesis of substituting parts of the brain, the identity of an all-prosthetic man.